2008
DOI: 10.1002/ijc.24050
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndromes and acute myeloid leukemia in cats infected with feline leukemia virus clone33 containing a unique long terminal repeat

Abstract: Feline leukemia virus (FeLV) clone33 was obtained from a domestic cat with acute myeloid leukemia (AML). The long terminal repeat (LTR) of this virus, like the LTRs present in FeLV from other cats with AML, differs from the LTRs of other known FeLV in that it has 3 tandem direct 47-bp repeats in the upstream region of the enhancer (URE). Here, we injected cats with FeLV clone33 and found 41% developed myelodysplastic syndromes (MDS) characterized by peripheral blood cytopenias and dysplastic changes in the bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
(83 reference statements)
0
18
0
Order By: Relevance
“…Myelodysplastic syndrome (MDS), characterized by peripheral blood cytopenias and dysplastic changes in the bone marrow, is a pre-stage of acute myeloic leukemia. It was found that changes of the LTR region of the FeLV genome (presence of three tandem direct 47-bp repeats in the upstream region of the enhancer ( URE )) are strongly associated with the induction of MDS [76]. Myelofibrosis, another cause of bone marrow suppression, is a condition characterized by abnormal proliferation of fibroblasts resulting from chronic stimulation of the bone marrow, such as chronic bone marrow activity from hyperplastic or neoplastic regeneration caused by FeLV.…”
Section: Clinical Signsmentioning
confidence: 99%
“…Myelodysplastic syndrome (MDS), characterized by peripheral blood cytopenias and dysplastic changes in the bone marrow, is a pre-stage of acute myeloic leukemia. It was found that changes of the LTR region of the FeLV genome (presence of three tandem direct 47-bp repeats in the upstream region of the enhancer ( URE )) are strongly associated with the induction of MDS [76]. Myelofibrosis, another cause of bone marrow suppression, is a condition characterized by abnormal proliferation of fibroblasts resulting from chronic stimulation of the bone marrow, such as chronic bone marrow activity from hyperplastic or neoplastic regeneration caused by FeLV.…”
Section: Clinical Signsmentioning
confidence: 99%
“…FeLV has been shown to induce many diseases in cats, such as lymphoma, myelodysplastic syndromes (MDS), acute myeloid leukemia (AML), aplastic anemia, and immunodeficiency (1,2). The primary translation product of the FeLV env gene is processed through proteolytic cleavage into two functional units: the surface unit (SU) and the transmembrane unit (TM).…”
mentioning
confidence: 99%
“…FeLV isolated from lymphomas typically contain two or three tandem direct repeats of enhancer elements in the LTR Matsumoto et al, 1992;Miura et al, 1989). Other repeated elements, such as the upstream region of the enhancer, have been reported in FeLVs isolated from cases of myelodysplastic syndrome or acute myeloid leukemia (Hisasue et al, 2009;Nishigaki et al, 2002;Nishigaki et al, 1997) and a 21-bp triple repeat was reported in cases of non-T-cell disease (Athas et al, 1995;Levesque et al, 1990). Using the primary translation product of FeLV env, the virus can be categorized into several subgroups based on its interference and host range properties (Jarrett et al, 1973;Sarma and Log, 1971;Sarma and Log, 1973).…”
Section: Introductionmentioning
confidence: 94%
“…* myelodysplastic syndromes, acute myeloid leukemia, aplastic anemia, and immunodeficiency (Hisasue et al, 2009;Mackey et al, 1975;Miura et al, 1987;Overbaugh et al, 1988a;Rohn et al, 1994;Rojko et al, 1979;Tzavaras et al, 1990). The genome of FeLV contains gag, pol, and env gene regions, which encode internal structural proteins, enzymes, and envelope proteins, respectively.…”
Section: Introductionmentioning
confidence: 98%